THE APPLICATION OF BEHAVIORISTIC THEORY AND ITS IMPLICATIONS IN ISLAMIC RELIGIOUS EDUCATION - Ningtiyas, Adisty; Suryana, Ermis; Zulhijra, Zulhijra (Jurnal Konseling Pendidikan Islam, 2026)
Islamic education requires an effective approach to shaping students' character and behavior, one of which is through behaviorist learning theory, which emphasizes the relationship between stimulus and response. Although widely used, the application of this theory in the context of Islamic Religious Education (PAI) still faces various challenges, such as a lack of student creativity and suboptimal reinforcement that supports positive behavioral change. This study aims to analyze the implications of behaviorist theory in Islamic Religious Education (PAI) learning and identify its advantages and disadvantages. The type of research is library research using content analysis techniques. Data were collected from written sources related to behaviorist theory and PAI learning, then analyzed systematically. The results show that behaviorist theory is effective in shaping student behavior and discipline, but tends to limit the space for creativity and innovation. The main obstacles include a lack of teacher motivation and adequate facilities. In conclusion, this theory is relevant for implementation, but needs to be combined with other approaches to make the learning process more enjoyable and sustainable.